Assisted reproductive techniques do not impact late neurodevelopmental outcomes of preterm children - Lefebvre, Tiphaine; Flamant, Cyril; Olivier, Marion; Gascoin, Géraldine; Bouet, Pierre-Emmanuel; Roze, Jean-Christophe; Barrière, Paul; Fréour, Thomas; Muller, Jean-Baptiste (Frontiers in Pediatrics, 2023)
Objective Assisted reproductive technology (ART) increases the rate of preterm births, though few studies have analyzed outcomes for these infants. No data are available on 4-year-old children born prematurely after ART. The objective was to investigate whether ART affect the neurodevelopmental outcomes at 4 years in preterm infants born before 34 weeks of gestational age (GA). Methods and results A total of 166 ART and 679 naturally conceived preterm infants born before 34 weeks GA between 2013 and 2015 enrolled in the Loire Infant Follow-up Team were included. Neurodevelopment was assessed at 4 years using the age and stage questionnaire (ASQ) and the need for therapy services. The association between the socio-economic and perinatal characteristics and non-optimal neurodevelopment at 4 years was estimated. After adjustment, the ART preterm group remained significantly associated with a lower risk of having at least two domains in difficulty at ASQ: adjusted odds ratio (aOR) 0.34, 95% confidence interval (CI) (0.13–0.88), p = 0.027. The factors independently associated with non-optimal neurodevelopment at 4 years were male gender, low socio-economic level, and 25–30 weeks of GA at birth. The need for therapy services was similar between groups (p = 0.079). The long-term neurodevelopmental outcomes of preterm children born after ART are very similar, or even better than that of the spontaneously conceived children.